Autograft versus BMPs for the treatment of non-unions: what is the evidence? - Blokhuis, Taco; Calori, Giorgio Maria; Schmidmaier, Gerhard (Injury, 2013)
Autograft is considered the gold standard in non-union treatment. However, it is associated with significant morbidity and limited biological activity. The introduction of bone morphogenetic proteins (BMPs) has added a valuable tool to the surgeon's possibilities. The initial expectations of the effectiveness of BMPs were high, but over the years the union rate of BMPs was shown to be comparable with autograft. In this overview, both treatment modalities are compared. The off-label use of BMPs, the combination of BMPs and autograft, and the economic perspective of BMP use are summarized. In their current formulation, BMPs are an effective alternative for autograft in selected cases. The beneficial effect outweighs the economic costs. Widening of the indication to other long bone non-unions and new formulations are expected in the nearby future.
Gesehen am 27.11.2020